1995
DOI: 10.1073/pnas.92.8.3194
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery of erythropoietin in mice by genetically modified skin fibroblasts.

Abstract: We have examined whether the secretion of erythropoietin (Epo) from genetically modified cells could represent an alternative to repeated injections of the recombinant hormone for treating chronic anemias responsive to Epo. Primary mouse skin fibroblasts were transduced with a retroviral vector in which the murine Epo cDNA is expressed under the control of the murine phosphoglycerate kinase promoter. "Neo-organs" containing the genetically modified fibroblasts embedded into collagen lattices were implanted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 23 publications
1
37
1
Order By: Relevance
“…Several studies have shown long-term expression of recombinant Epo, following the transduction of autologous fibroblasts 18 or myoblasts 20 with retroviral vectors or direct injections of either adenoviral vectors [22][23][24] or adenoassociated viral vector. 25 However, until now, only ex vivo transduction of hematopoietic cells, genetically modified by a retroviral vector, has been shown to increase durably hematocrit and to improve the red cell phenotype of ␤-thalassemic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown long-term expression of recombinant Epo, following the transduction of autologous fibroblasts 18 or myoblasts 20 with retroviral vectors or direct injections of either adenoviral vectors [22][23][24] or adenoassociated viral vector. 25 However, until now, only ex vivo transduction of hematopoietic cells, genetically modified by a retroviral vector, has been shown to increase durably hematocrit and to improve the red cell phenotype of ␤-thalassemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 myoblasts were engineered to secrete high levels of mEpo by transfection with pPImEpo-Neo-DHFR vector described previously, 18 in which hEpo cDNA was replaced by mEpo cDNA. Cells were encapsulated in microporous polyethersulfone hollow fibers (10 mm × 0.6 mm), 18,26 and differentiated by placing the capsules in 10% Prolifix (BioMedia, Boussens, France) differentiation medium for 3 days. Each capsule was loaded with 2 × 10 5 cells.…”
Section: Encapsulated Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells engineered to secrete one or several angiogenic proteins could be introduced at the site of ischemia to stimulate new vessel growth. Myoblasts 21,22 and fibroblasts 23 have been employed in the past to systemically deliver proteins such as erythropoietin and human growth hormone by direct cell transplantation. Ideally, for an angiogenesisbased therapy, it would be desirable to halt treatment after ischemic tissue is revascularized, as prolonged exposure to angiogenic factors could be deleterious.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Retrovirus-mediated gene transfer into primary skin fibroblasts has provided measurable amounts of therapeutic proteins in animal models, including adenosine deaminase (ADA), 26,27 factor IX, 28,29 ␤-glucuronidase 30,31 and erythropoietin. 32 A major problem emerging from experiments using skin equivalent grafts was the limited time of vector-encoded gene expression once transduced cells were implanted in vivo. We have shown in both rats and dogs that vector-derived gene expression was diminished at between 3 and 4 weeks despite the long-term presence of vector sequences in transplanted cells.…”
Section: -11mentioning
confidence: 99%